Calpain in ovarian cancer progression and chemotherapeutic response - Zhang, Siwei (2018)
The calpain system is associated with cancer chemotherapeutic response in both in vivo and in vitro studies. Previous immunohistochemistry (IHC) data conducted in our group indicated that high calpain-2 expression was associated with both the resistance to platinum-based adjuvant chemotherapy and worse patient outcome; moreover calpain-2 appeared as an independent prognostic factor in multivariate analysis.